TAHKİMDE İPTAL DAVASI VE İPTAL DAVASININ AMAÇLARI BAKIMINDAN BAZI DEĞERLENDİRMELER - (:unkn) unknown (My University, 2016)
Türk Tahkim hukukunda ortaya çıkan hakem kararlarından; taraflardan en az birinin memnun olmaması ve iptal edilmesini talep etmesi halinde, söz konusu kararın ne şekilde iptal edilebileceği, iptal sebepleri ve süreci bu çalışmada ortaya konulmaya çalışılmıştır.

When at least one of the parties is not satisfied with an arbitral award under Turkish Law, revocation of arbitral award is requested. This study aims to examine how an arbitral award can be revoked. Within this framework, reasons for revocation, and the procedure of revocation are studied.
The Case of Revocation of Arbitral Awards and For The Purposes of Some of The Reviews of The Arbitration Case of Revocation
Keywords: Hukuk